2023
DOI: 10.3390/biomedicines11030754
|View full text |Cite
|
Sign up to set email alerts
|

Human Plasma Xanthine Oxidoreductase Activity in Cardiovascular Disease: Evidence from a Population-Based Study

Abstract: Xanthine oxidoreductase (XOR) and its products contribute to the development of chronic inflammation and oxidative stress. Excessive XOR activity is believed to promote inflammatory responses and atherosclerotic plaque formation, which are major cardiovascular risk factors. The mechanisms of XOR activity in the development and progression of cardiovascular disease (CVD), coupled with the complexity of the relationship between XOR activity and the biological effects of uric acid; reactive oxygen species; and ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 75 publications
0
1
0
Order By: Relevance
“…In addition, through enrichment analysis, NOX4, PARP14, and their related genes are mainly enriched in oxidative stress, metabolic processes, the immune system, and the VEGFA-VEGFR2 signaling pathway, etc. Studies have confirmed that destructive oxidative stress is one of the important mechanisms for the occurrence and development of DR and AS [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, through enrichment analysis, NOX4, PARP14, and their related genes are mainly enriched in oxidative stress, metabolic processes, the immune system, and the VEGFA-VEGFR2 signaling pathway, etc. Studies have confirmed that destructive oxidative stress is one of the important mechanisms for the occurrence and development of DR and AS [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma XOR activity has also been proposed as a possible risk factor for CVD. However, the authors believe that more research is needed to gain an understanding of the mechanisms of plasma XOR activity and the development of CVD [24].…”
Section: Published Articlesmentioning
confidence: 99%
“…Japanese population studies have suggested that plasma XO activity could serve as a reliable biomarker for CVDs. Furthermore, XO activity and subsequent production of UA and ROS have been implicated in promoting the early stages of CKD by affecting microcirculation, causing tissue damage, and contributing to micro-artery dysfunction and hypertension [111,112]. Furthermore, the foam cells enhance the production of inflammatory cytokines, therefore aggravating the inflammation.…”
Section: Uric Acidmentioning
confidence: 99%